Triangulating transmediality: A multimodal semiotic framework relating media, modes and genres. (December 2017) - Bateman, John A.
Abstract: A prerequisite for approaching the study of changes across media and their evolving roles in society, especially when 'new' media emerge, is that one has a good theoretical grasp of just what 'media' are and how they may be approached analytically. To support insightful analysis going beyond description and cataloguing, there is a need to make current notions far more precise. In this paper, I evaluate some of the more developed proposals made for characterizing relations between media to date and argue that a more explicit and refined semiotic foundation has much to offer. Only with such a foundation can sufficiently fine-grained theoretical and methodological tools be constructed capable of tracking both media evolution and media interrelationships in detail. The paper concludes that the incorporation of a particular definition of semiotic modes in the context of multimodality allows more discriminating characterizations of 'media' and 'mediality' in general.